Online Banking and Customer Satisfaction: Evidence from India. (March 2019) - Banu, A. Meharaj; Mohamed, N. Shaik; Parayitam, Satyanarayana
On the basis of technology acceptance model (TAM) and decomposed theory of planned behaviour (DTPB), the present study is aimed at studying customer satisfaction in online banking in India. Data collected from 750 respondents from both public and private sector banks were used to test the mediated model using the hierarchical regression. The results supported that perceived usefulness acted as a partial mediator in the relationship between various independent variables, such as awareness of online banking services, security, knowledge of Internet, self-efficacy, intention to adopt, trust, easy to use, and dependent variable, that is, customer satisfaction. Implications for research and practising managers are discussed.